2020
DOI: 10.1186/s12879-020-4883-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Candida albicans and non-albicans Candida species isolated in different clinical samples and their in vitro antifungal suscetibity profile in Ethiopia

Abstract: Background: The spectrum of yeasts and their antifungal susceptibility profile are poorly known and treatment of fungal disease has remained empirical. The aim of this study is to determine the spectrum and antifungal susceptibility profile of yeasts particularly of Candida species.Methods: A descriptive study on the composition of Candida species and antifungal susceptibility profile were conducted from January 2018 to September 2018. Clinical samples collected from different sites were cultured on Sabouraud … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 40 publications
2
28
1
3
Order By: Relevance
“…A total of six species of Candida were identified and are in order of frequency C. albicans, C. tropicalis group I, C. parapsilosis group I (C. parapsilosis), C. parapsilosis group II (known as C. orhtopsilosis), C. kefyr and C. lusitaniae. These results were similar to those reported from other African countries [7,9,[12][13][14].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A total of six species of Candida were identified and are in order of frequency C. albicans, C. tropicalis group I, C. parapsilosis group I (C. parapsilosis), C. parapsilosis group II (known as C. orhtopsilosis), C. kefyr and C. lusitaniae. These results were similar to those reported from other African countries [7,9,[12][13][14].…”
Section: Discussionsupporting
confidence: 92%
“…Although C. albicans remains the most represented species in candidiasis, there is an emergence of NAC species in mycosis. Among these species, C. tropicalis, C. glabrata, C. krusei, C. parapsilosis, C. kefyr and C. lusitaniae have been the most reported [3,4,7,8]. In Senegal, it has been reported that Candida albicans is the predominant species [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Candida spp. cause infections that range from non-life-threatening mucosal illnesses to invasive fatal infections, such as bloodstream infections [ 4 ]. Nosocomial infection by Candida is a problematic issue worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados evidenciados sugerem que o óleo essencial de B. milleflora pode ter ação junto ao processo de transição morfológica fúngica das espécies de Candida, considerando que os fungos pertencentes a esta espécie estão entre os principais causadores de infecções fúngicas (HAMMED et al, 2018;ZHANG et al, 2018;SEYOUM et al, 2020), a redução de um de seus fatores de virulência, contribui para o desenvolvimento de terapêuticas inovadoras que possam reduzir os efeitos da invasão por patógenos fúngicos no organismo humano.…”
Section: Resultados E Discussõesunclassified
“…O aumento da resistência aos antimicrobianos já existentes, justificam as pesquisas por fontes alternativas de tratamento, diversas espécies de vegetais têm apresentado potencial antimicrobiano promissor, sendo alvo de estudos que visam avaliar os possíveis compostos com eficácia contra os micro-organismos resistentes e que tenham baixa toxicidade para o hospedeiro (BONI et al, 2017). Os fungos são patógenos associados a infecções de difícil tratamento no organismo humano, fungos da espécie Candida são descritos como micro-organismos oportunistas, pois estão presentes no organismo humano de forma comensal, porém mediante condições de queda da imunidade apresentam aumento da patogenicidade e potencial invasor dos tecidos do hospedeiro (SEYOUM et al, 2020;SHAHABUDIN;AZMI, 2020).…”
Section: Introductionunclassified